IMPLEMENTASI PENILAIAN AUTENTIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MURID KELAS II SDN 1 KEBONAGUNG - Kireina Alifa; Amir Mukminin (Al-Irsyad: Jurnal Pendidikan Agama Islam, 2025)
This research examines the implementation of authentic assessment in Islamic Religious Education learning for second-grade students at SDN 1 Kebonagung. Authentic assessment, as a comprehensive approach, aims to measure students' abilities in real-world contexts. The research employs a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Results indicate that the implementation of authentic assessment in Islamic Religious Education for second-grade students at SDN 1 Kebonagung encompasses attitude assessment (observation, self-assessment, and journals), knowledge assessment (oral tests, written tests, and assignments), and skills assessment (performance and portfolio). Write abstract in English.